2008
DOI: 10.1136/adc.2007.123653
|View full text |Cite
|
Sign up to set email alerts
|

The 6-minute walk test: normal values for children of 4-11 years of age

Abstract: Performing a 6MWT is feasible and practical in young children. This study provides data on normal children against which the performance of sick children and the response to therapeutic intervention can be judged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

44
217
15
32

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(308 citation statements)
references
References 26 publications
44
217
15
32
Order By: Relevance
“…Mean baseline walking distance was 372 m, considerably more than the values of around 200 m seen in the phase 3 study [Hendriksz et al, [Link]]. The fact that walking distances were closer to normal in this patient group (i.e., 70–80% of that of an unaffected population [Lammers et al, 2008; Li et al, 2007]) may have made it more challenging to show improvement and could possibly account for the lack of change in 6MWT distance in this study. Also, these patients can probably not be expected to reach 6MWT distances comparable to healthy (unaffected) age/height‐matched controls due to the presence of skeletal and joint abnormalities.…”
Section: Discussionmentioning
confidence: 91%
“…Mean baseline walking distance was 372 m, considerably more than the values of around 200 m seen in the phase 3 study [Hendriksz et al, [Link]]. The fact that walking distances were closer to normal in this patient group (i.e., 70–80% of that of an unaffected population [Lammers et al, 2008; Li et al, 2007]) may have made it more challenging to show improvement and could possibly account for the lack of change in 6MWT distance in this study. Also, these patients can probably not be expected to reach 6MWT distances comparable to healthy (unaffected) age/height‐matched controls due to the presence of skeletal and joint abnormalities.…”
Section: Discussionmentioning
confidence: 91%
“…However, the prevalence of sedentary lifestyle (52.23%) and obesity (12.5%) observed in the present study population agrees with the values previously reported for healthy Brazilian subjects (21,35). In addition, convenience samples have often been included in studies evaluating reference values for 6MWD (1,(4)(5)(6)(7)(8)10,28,29). Although the sample size was sufficient to elaborate a reference equation, we evaluated a relative small sample in the present study to produce reference values.…”
Section: Discussionmentioning
confidence: 99%
“…The American Thoracic Society (ATS) recommends that researchers establish specific reference values for each population (3). Recent studies have defined 6MWT reference values for various populations (6)(7)(8)(9)(10). However, previous studies have shown that equations used in other populations are not necessarily applicable to Brazilian subjects (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Dentro de éstas se describen: el propósito, indicaciones, limitaciones, contraindicaciones, seguridad y aspectos técnicos específicos 3 . La creciente utilización del TM6 en la práctica clínica ha llevado a la realización de diversos estudios para unificar criterios en la aplicación del test y establecer valores de referencia en personas sanas que faciliten la comparación con pacientes que presenten patologías, principalmente de carácter crónico [5][6][7][8][9][10][11][12][13][14][15] . En población adulta existen múltiples estudios publicados que han permitido establecer valores normales [11][12][13][14] .…”
unclassified
“…En población adulta existen múltiples estudios publicados que han permitido establecer valores normales [11][12][13][14] . En pediatría ha sido utilizado en niños sanos [4][5][6]9,10,15 , en pacientes con fibrosis quística 7,8 , bronquiolitis obliterante 16 , cardiopatías y trasplantes cardiacos y/o pulmonares, así como también, en intervenciones terapéuticas 17 . Sin embargo, aún sigue siendo poco utilizado en población pediátrica y la falta de valores de referencia ha dificultado su interpretación.…”
unclassified